Which Occupations Do Jobseekers and Firms Look For? Evidence from Three Public Employment Services - Pedro S. Martins (Global Labor Organization (GLO), 2021)
This study proposes and applies a new methodology to analyse firms' and workers' occupational preferences. We use microdata covering all 2014-2018 vacancy and jobseeker registrations from the Public Employment Services of Belgium, Morocco, and South Korea. We find that a small number of occupations are responsible for a large share of registrations and may thus deserve particular attention. We also find considerable stability in occupation preferences (especially by jobseekers) but that the correlation between firms' and workers' preferences weakens over time. Finally, we find different responsiveness levels of jobseeker preferences to vacancy gaps. However, young jobseekers do not appear to respond more quickly to such gaps.
Keywords: J24; J62; J68; 330; Labour adjustment; Occupations; Job search; Vacancy gaps